2003
DOI: 10.1016/s0014-5793(03)00107-8
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model for determination of parameters of helical structures in solution by small angle scattering: comparison of RecA structures by SANS

Abstract: The ¢lament structures of the self-polymers of RecA proteins from Escherichia coli and Pseudomonas aeruginosa, their complexes with ATPQ QS, phage M13 single-stranded DNA (ssDNA) and the tertiary complexes RecA: :ATPQ QS: :ss-DNA were compared by small angle neutron scattering. A model was developed that allowed for an analytical solution for small angle scattering on a long helical ¢lament, making it possible to obtain the helical pitch and the mean diameter of the protein ¢lament from the scattering curves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…4 , squares) showed the typical for rod‐like particles 1 / q dependency in the low scattering angles and the local minimum near 0.07 Å −1 and a maximum near 0.09 Å. This scattering pattern was similar to that observed in the earlier SANS studies of RecA protein filaments [4,5] where this feature of the spectrum was associated with the helix periodicity. The position of the minimum (real space length of 90 Å) is close to that expected for the stretched form of RecA filament, corresponding to the presynaptic complex.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4 , squares) showed the typical for rod‐like particles 1 / q dependency in the low scattering angles and the local minimum near 0.07 Å −1 and a maximum near 0.09 Å. This scattering pattern was similar to that observed in the earlier SANS studies of RecA protein filaments [4,5] where this feature of the spectrum was associated with the helix periodicity. The position of the minimum (real space length of 90 Å) is close to that expected for the stretched form of RecA filament, corresponding to the presynaptic complex.…”
Section: Resultssupporting
confidence: 83%
“…RecA polymer is a helical filament with the pitch of approximately 90-95 Å and ca. 100 Å in diameter [3][4][5]. Filaments become more abundant on damaged DNA regions in stress, which initiates the so called SOS function of RecA.…”
Section: Introductionmentioning
confidence: 99%
“…Low-concentration solutions of hen egg white lysozyme (HEWL) amyloid fibrils based on mixtures of light (H 2 O) and heavy (D 2 O) water were considered. We found that the model of a helix composed of spherical homogeneous units, first proposed by Lebedev et al (2003) to characterize the helical aggregation of RecA protein, also represents quite well the main features of the scattering curves from the protofilament structure of HEWL amyloids. Additionally, the indirect Fourier transform procedure, which takes into account the elongated form of the studied protofilaments, was used to get information about their cross-section structure.…”
Section: Introductionmentioning
confidence: 57%
“…Traditionally, the models of a cylinder and a hollow cylinder are probed first for elongated helical particles (Oliveira et al, 2009;Lebedev et al, 2003). We demonstrate how these two models work in Fig.…”
Section: Small-angle Neutron Scatteringmentioning
confidence: 85%
“…Two-detector system has no such disadvantage. The need of high resolution at the nearest position for the wide spectrum of samples (alconates [15], proteins [16][17][18][19], dendrimers [20][21][22][23][24][25], nanotubes [26], lipids [27][28][29]) leads to conducting the experiments at the nearest position of the well-collimated detector. Consequently the time of measurements range on the spectrometer YuMO is from 3 min [30,31] up to 12h [32,33].…”
Section: The Comparison Of the Time Of Measurements: One Detector At mentioning
confidence: 99%